(untitled) (Research, Society and Development, 2021)
Introduction: Pregnancy-Specific Hypertensive Disease (DHEG) is determined as a multisystem disease, which has the diagnosis of arterial hypertension in pregnancy, blood pressure levels should be equal to or greater than 140/90mmHg, which may be: preeclampsia, when these levels appear after the 20th week, being a syndrome that has no cure, except for the interruption of pregnancy, making the case more severe when HELLP Syndrome has evolved. Objective: To analyze the prevalence of Specific Hypertensive Disease of Pregnancy (DHEG) between the years 2019 and 2020 in the municipality of Porto Franco - MA. Methodology: The study is descriptive, exploratory, documentary, retrospective, with a quantitative approach to the data. The research was carried out in five Basic Health Units in the municipality of Porto Franco - Maranhão. Results and discussion: The diagnosis of DHEG identified from the 20th of pregnancy was shown in 88% and 12% above the 25th week. 88% had family history of hypertension, diabetes and heart diseases, against 12% who did not, 77% of the women underwent the tests and 66% of these women received follow-up from a doctor, nurse and community health agent. The findings of this disease are to avoid possible sequelae for the mother and fetus, and the role of nurses in initial prenatal consultations is important to prevent possible complications. Conclusions: Therefore, it is worth affirming that a qualified, humanized and specialized prenatal care is fundamental in the control of Cases of DHEG, since when performed correctly, the rate of treatment is performed.